Flexible stab-resistant material as well as preparation method and application thereof
By modifying the surface of aramid fiber and combining it with the resin glue system, the problems of insufficient performance of existing sting-proof materials in high-temperature and low interface bonding strength are solved, and high-performance, lightweight, thermally stable flexibility is achieved Sharp-proof materials meet the requirements of the new standards and reduce production costs.
Patent Information
- Application Number
- CN202411262122.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing stabbing materials are difficult to meet the stabbing performance requirements in high temperature, low temperature and water-soaked environments. At the same time, their low interface bonding strength leads to poor stability, and the total mass is difficult to meet the new standard below 1.8kg.
The surface modification of the aramid fibers is carried out using nano-aramid aqueous dispersion or aramid slurry, and composited with a high-performance resin glue system. The highly dispersed aramid slurry is prepared through low-temperature solution polymerization technology to improve the interface bond between the fiber and the resin matrix. Strength, forming a flexible, high-performance anti-sting material.
It realizes the high thermal stability and lightweight flexibility of the stabbing materials, meets the requirements of higher stabbing performance, reduces production energy consumption, and realizes the application of domestic materials.
Smart Images

Figure CN119119728A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional composite materials, and in particular relates to a flexible stab-proof material and a preparation method and application thereof. Background Art
[0002] Stab-resistant clothing for police can effectively prevent the body from being hurt by controlled knives, and at the same time ensure personal safety when dealing with violent terrorist incidents, and gradually become an essential protective equipment for police officers to perform their duties. Stab-resistant clothing mainly consists of stab-resistant layer, buffer layer, outer coat and other parts. For stab-resistant performance, all countries have clear requirements. The more representative stab-resistant clothing product standards mainly include my country's GA 68-2019 "Police Stab-resistant Clothing", the United States' NIJ 0115.00 "Stabresistance of personal body armor" (2000), the United Kingdom's HOSDB Body armour standards for UK Police (2017) and Germany's SCHUTZKLASSE (2008). Among them, the test tool material is mainly stainless steel and alloy steel, with a hardness of 50-55HRC. The GA68-2019 Class A stab-proof standard uses a D1 tool with an impact energy of 24±0.5J. It needs to meet the application requirements in different environments, namely high temperature (55℃, 4h), low temperature (-20℃, 4h), normal temperature (room temperature) and immersion in water (immersion in water for 30min), and has specific requirements for appearance, color, protection area, thickness of the stab-proof layer and quality. With the advancement of technology and the development of materials, the promulgated and implemented GA68-2024 has further requirements for the quality of stab-proof clothing. It adjusts the weight of stab-proof clothing in GA68-2019 from ≤2.8kg to ≤1.8kg, and adds relevant requirements for bending, that is, the force is ≤180N when bending 20mm in the direction of the body-fitting surface. The above requirements have put forward higher requirements on the performance of stab-proof materials. Therefore, the development of lightweight, flexible and high-performance stab-proof materials is the material basis for the design and preparation of new police stab-proof clothing and bulletproof and stab-proof clothing, and it is also an urgent need.
[0003] The development of stab-proof materials provides a material basis for the design and preparation of stab-proof clothing, especially for the development of multifunctional protective clothing (such as bulletproof and stab-proof clothing, stab-proof life jackets, etc.). According to their materials, stab-proof materials can be divided into metal and non-metallic stab-proof materials. Among them, metal materials have high density, poor flexibility, and are prone to corrosion. At this stage, they are rarely used alone as stab-proof materials. Fibers with high modulus and high strength, such as aramid and ultra-high molecular weight polyethylene, show excellent performance in impact resistance, wear resistance, and cutting resistance, and are becoming the main material of new flexible stab-proof clothing.
[0004] In the prior art, Chinese invention patent document ZL 202310546450.X discloses a multifunctional stab-proof clothing, which first grafts silica and melamine onto graphene oxide, and then prepares modified ultra-high molecular weight polyethylene fiber through blending modification, and then prepares the modified ultra-high molecular weight polyethylene fiber and aramid fiber into a non-woven fabric, and then stacks the non-woven fabric into a stab-proof chip; the multifunctional stab-proof clothing assembled from the stab-proof chip has anti-static and flame retardant properties, and can meet the stab-proof performance test requirements of the Ministry of Public Security GA68-2019. However, the surface density of the stab-proof chip described in the patent document is 6-9kg / m 2 The quality of the stab-proof material is difficult to meet the protection area ≥ 0.25m 2 , the technical requirement of total mass ≤1.8kg, and its interface bonding strength may not be high, which leads to poor stability of the material. Summary of the invention
[0005] In view of this, the purpose of the present invention is mainly to provide a new type of flexible stab-proof material and its preparation method and application. The stab-proof material provided by the present invention has high thermal stability and is flexible and lightweight, and can meet higher requirements of the standards.
[0006] The present invention provides a method for preparing a flexible stab-proof material, comprising the following steps:
[0007] Providing a nano-aramid aqueous dispersion or an aramid slurry, wherein the aramid slurry comprises an aramid resin, an amide solvent and a cosolvent;
[0008] The nano-aramid aqueous dispersion or aramid slurry is used to modify the surface of aramid fibers by dipping to form a functionalized aramid fabric, which is then compounded with a resin adhesive system comprising a benzoxazine resin, an epoxy resin and a curing agent to obtain a flexible stab-proof material.
[0009] In some embodiments of the present invention, the aramid slurry has a solid content of 5-7 wt % and an intrinsic viscosity of 3.0-3.6 dL / g.
[0010] In some embodiments of the present invention, the aramid slurry is obtained by the following operation: phenylenediamine and phthaloyl halide are polymerized through low-temperature solution, and then neutralized, impurity-removed and diluted to obtain an aramid slurry containing aramid resin.
[0011] In some embodiments of the present invention, the aramid resin is para-aramid, the amide solvent is N,N-dimethylformamide, and the co-solvent is calcium chloride.
[0012] In some embodiments of the present invention, the surface modification includes: selecting para-aramid fiber filaments or para-aramid fiber fabrics, immersing them in the nano-aramid aqueous dispersion or aramid slurry for a residence time of 3 minutes, then shaping them in a coagulation bath, washing and drying to obtain functionalized aramid fibers.
[0013] In some embodiments of the present invention, the strength of the para-aramid fiber filament is ≥16 cN / dTex, the functionalized aramid fiber is processed into a functionalized aramid fabric, and the surface density of the functionalized aramid fabric is 165-260 g / m 2 .
[0014] In some embodiments of the present invention, the benzoxazine resin is one or more of bisphenol A benzoxazine, bisphenol F benzoxazine, MDA benzoxazine, ODA benzoxazine and composite benzoxazine; the epoxy resin is bisphenol A epoxy resin; the curing agent is one or more of dicyandiamide, 4,4-diaminodiphenyl sulfone, polyamide, isophordione diamine, and diaminodiphenylmethane.
[0015] In some embodiments of the present invention, the compounding with the resin adhesive system comprises: immersing the functionalized aramid fabric in a resin adhesive, drying, and controlling the adhesive amount to be 45-50wt%; the resin adhesive comprises benzoxazine resin, epoxy resin, curing agent, flame retardant, silane coupling agent and solvent;
[0016] The semi-cured sheet obtained after drying is pressed at a temperature of 130 to 160 degrees Celsius, and the pressing pressure is 5 to 20 MPa to obtain a flexible stab-proof material.
[0017] Accordingly, the present invention provides a flexible stab-resistant material obtained by the preparation method as described above.
[0018] In addition, the present invention also provides the use of the flexible stab-proof material as described above in security clothing and accessories.
[0019] Compared with the prior art, the present invention provides a new stab-proof material and a preparation method thereof, that is, the surface of aramid fiber is modified by using nano-aramid aqueous dispersion or aramid slurry, and then compounded with a high-performance resin adhesive system to obtain a new flexible stab-proof material. The present invention is committed to the development of lightweight and flexible stab-proof materials. It is preferred to use low-temperature solution polymerization technology to prepare highly dispersed aramid slurry, and directly use the aramid slurry to homogenize and modify the intrinsic surface of aramid fiber or fabric by impregnation, which can improve the interfacial bonding strength between the fiber and the resin matrix, thereby improving the stab-proof performance of the stab-proof material. The present invention compounds the modified functional aramid fabric with a resin adhesive system with benzoxazine resin as the main resin to obtain a high-performance, flame-retardant and stab-proof composite material. The embodiment of the present invention uses only stab-proof materials for testing, and such materials can also be used in safety protection clothing such as bulletproof and stab-proof clothing and corresponding accessories.
[0020] Preferably, the embodiment of the present invention adopts a composite resin system and a composite curing system, which can effectively reduce the curing temperature of benzoxazine resin (the curing procedure of benzoxazine is generally 180°C, 30min, then 200°C, 3h, and finally 220°C, 2h), reducing energy consumption in the production process. At the same time, the requirements for equipment and auxiliary materials are further reduced, that is, general flat hot pressing equipment and ordinary pressing auxiliary materials (isolation film) can be used for production. The present invention can use domestic aramid fiber and domestic resin system to prepare lightweight and flexible stab-proof materials, thereby realizing the nationalization of application products such as police stab-proof clothing. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The curing peak temperature fitting curve of the resin system of the embodiment of the present invention;
[0022] Figure 2 The DSC curves of the samples of Example 1 and Example 2 of the present invention;
[0023] Figure 3 This is the dipping condition of the samples of Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.
[0025] The present invention provides a method for preparing a flexible stab-proof material, comprising the following steps:
[0026] Providing a nano-aramid aqueous dispersion or an aramid slurry, wherein the aramid slurry comprises an aramid resin, an amide solvent and a cosolvent;
[0027] The nano-aramid aqueous dispersion or aramid slurry is used to modify the surface of aramid fibers by dipping to form a functionalized aramid fabric, which is then compounded with a resin adhesive system comprising a benzoxazine resin, an epoxy resin and a curing agent to obtain a flexible stab-proof material.
[0028] The present invention provides a novel stab-proof material and a preparation method thereof. The stab-proof material can be used as a stab-proof material for personal protective equipment, has high thermal stability, and is flexible and lightweight, can meet higher requirements of standards, and is convenient for application.
[0029] The stab-proof material described in the embodiment of the present invention involves the following preparation process: The embodiment of the present invention first synthesizes an aramid slurry, which is used to modify aramid fibers. In the embodiment of the present invention, an amide solvent and a cosolvent can be added to a reaction kettle, the temperature is lowered to 0-5°C, a certain amount of p-phenylenediamine and terephthaloyl chloride are added thereto, the temperature of the reaction kettle is kept not exceeding 50°C during the reaction, the reaction time can be controlled to be 2-5h, and an aramid slurry containing a para-aramid resin is obtained after neutralization, impurity removal and dilution.
[0030] The present invention preferably adopts low-temperature polymerization technology to prepare a highly dispersed aramid slurry. The aramid resin is mainly para-aramid, and the amide solvent is preferably N,N-dimethylformamide, which has good comprehensive performance; the cosolvent can be selected from alkali or alkaline earth metal salts, preferably calcium chloride, which has a good cost performance. In some embodiments of the present application, 0.4 to 0.6 parts by mass of cosolvent can be added to 100 parts by mass of N,N-dimethylformamide; and 10 parts by mass of p-phenylenediamine are added. After fully dissolved, 18 to 19 parts by mass of terephthaloyl chloride can be added in 5 times to carry out polymerization reaction at low temperature. Here, the reaction temperature at low temperature is controlled within 50°C.
[0031] After the reaction is completed, the embodiment of the present invention can use calcium hydroxide to neutralize the HCl produced by the reaction until the pH of the solution is neutral (such as detected by a wetted pH test paper); then, the impurities are removed by vacuum filtration to obtain a highly dispersed aramid stock solution, wherein the solid content of the stock solution can be 15-17wt%; the aramid stock solution is further diluted with N,N-dimethylformamide to a solid content of 5-7wt% and an intrinsic viscosity of 3.0-3.6dL / g, and then transferred to a closed anaerobic container for storage and standby use.
[0032] In the prior art, fiber surface modification is rarely performed. Due to the high orientation and high crystallinity of aramid fibers and ultra-high molecular weight polyethylene fibers, their surface bonding strength with the resin matrix is relatively low, which leads to poor overall performance and stability of the material.
[0033] The embodiment of the present invention directly uses the obtained aramid slurry to perform surface modification on aramid fibers or fabrics by impregnation. The aramid slurry described in the present invention can partially break the strong hydrogen bonding of aramid macromolecules, and has higher efficiency and stability than the traditional surface adhesion modification method, that is, it can achieve embedded and bonded modification of aramid fibers, greatly improving the interfacial adhesion strength between the fiber and the resin matrix (which can be objectively evaluated by the single-filament pull-out force).
[0034] The embodiment of the present invention performs surface homogeneous modification treatment on aramid fiber, which is beneficial to improve the interfacial bonding strength between the fiber and the resin matrix. Specifically, the aramid fiber can be placed on a bracket for wiring, the above-mentioned aramid slurry is transferred into a glue tank, the aramid fiber is immersed in the aramid slurry through a guide roller, and the pulling rate is controlled to ensure that the fiber stays in the solution for 3 minutes; then, the aramid fiber pulled out of the glue tank is immersed in the first coagulation bath, which is composed of a DMAc / H2O mixed solution, wherein the CaCl2 content is 3wt%, and the aramid fiber pulled out of the first coagulation bath is also immersed in the second coagulation bath, which is composed of a DMAc / H2O mixed aqueous solution; the fiber pulled out of the second coagulation bath enters a water washing device for water washing, and then is dried, and the obtained functionalized aramid fiber is rolled up for standby use.
[0035] In some embodiments of the present invention, the selected aramid fiber is SF68 para-aramid filament (800D or 1000D) provided by Sinochem International, with a strength ≥16cN / dTex (for the fiber, the strength value has a certain degree of non-uniformity, and it is sufficient to satisfy the requirement of being above the minimum value after multiple measurements). After the aramid fiber is impregnated with aramid slurry, it is preferably shaped by a mixed solution of dimethylacetamide (DMAc) and water in different proportions; the first coagulation bath composition DMAc / H2O=70 / 30, wherein the content of CaCl2 is 3wt%, and the second coagulation bath composition DMAc / H2O=50 / 50. In addition, the washing and drying are operations well known to those skilled in the art. In the embodiments of the present invention, the aramid fiber is homogenized and intrinsically modified with para-aramid slurry, and the aramid fiber is debonded with DMAc salt solution; other embodiments may use nano-aramid aqueous dispersion to perform similar modifications on the aramid fiber.
[0036] In some embodiments of the present invention, a horizontal loom may be used to weave the functionalized aramid fibers to form a functionalized aramid fabric. For example, it is generally a plain weave fabric with a transverse density of 24 or 28 counts / 10 cm and a longitudinal density of 28 or 32 counts / 10 cm. A high weaving density has an improved effect on the stab-proof performance. The surface density of the woven aramid fabric is preferably controlled to be 165 to 260 g / m 2 , for example 165g / m 2 , 180g / m 2, 200g / m 2 , 220g / m 2 , 260g / m 2 In some other embodiments, the aramid fiber fabric may be surface modified in the same manner as the above steps.
[0037] Some embodiments of the present invention also use compounding technology to prepare resin glue, with benzoxazine resin and epoxy resin as the composite resin matrix. The main resin selected in the embodiment of the present invention is benzoxazine resin, which refers to a thermosetting resin containing N and O oxazine six-membered rings in the structure, which is inherently flame retardant and can be one or more of bisphenol A benzoxazine, bisphenol F benzoxazine, MDA benzoxazine, ODA benzoxazine and composite benzoxazine, preferably bisphenol A benzoxazine. The present invention has no specific requirements for the molecular weight of the resin, all of which are commercial products on the market, and the supplier can be Puyang Enying Polymer Materials Co., Ltd., etc. Bisphenol A type benzoxazine is made by dehydration condensation of bisphenol A, polyformaldehyde and aniline; bisphenol F type benzoxazine is a tough benzoxazine made by dehydration condensation of bisphenol F, polyformaldehyde and aniline; MDA type benzoxazine is a high heat-resistant benzoxazine made by dehydration condensation of diaminodiphenylmethane, polyformaldehyde and phenol; ODA type benzoxazine is 4,4'-diaminodiphenyl ether type benzoxazine (ODA-BOZ); the composite type refers to the compounding of two or more benzoxazine resins.
[0038] The epoxy resin in the resin glue of the embodiment of the present invention is preferably a bisphenol A epoxy resin, and further, the selected bisphenol A epoxy resin can be one or more of E20, E44 and E51. At the same time, the curing agent selected in the embodiment of the present invention can be one or more of dicyandiamide, 4,4-diaminodiphenyl sulfone, polyamide, isophorone diamine, diaminodiphenyl methane, preferably a composite curing system of 4,4-diaminodiphenyl sulfone (DDS) and isophorone diamine (IPDA). In addition, the solvent in the resin glue can be selected from N, N-dimethylformamide (DMF) or a mixed solution of propylene glycol monomethyl ether and acetone, preferably a mixed solution of propylene glycol monomethyl ether and acetone.
[0039] Furthermore, the resin adhesive of the specific embodiment of the present invention includes a flame retardant, and the flame retardant is selected from one or more of dimethyl methyl phosphate (DMMP), tris (2,3-dichloropropyl) phosphate (TCPP), ammonium polyphosphate (APP), and ammonium superphosphate, and may also include a silane coupling agent (such as KH560); the solid content of the resin adhesive is preferably 57 to 63wt%.
[0040] The preparation method of the resin glue of the preferred embodiment of the present invention includes: S1. adding 100 parts of benzoxazine resin to the reaction kettle, heating to 110°C until it is completely transparent; S2. cooling to 80°C, adding 40 parts of solvent (which is the mass fraction, for example, if the feed is 100g or 100kg, the corresponding solvent is 40g or 40kg), and then, adding 30 to 100 parts of epoxy resin according to the mass ratio; starting stirring, setting the speed to 600r / min, heating to 120°C, and keeping warm for 1-4h; S3. adding a measured part of curing agent 1 S4. Cool the mixture to below 40°C, continue stirring, adjust the speed to 600r / min, add 5 to 10 parts of a mixture of ammonium superphosphate and TCPP (mass ratio is 2:1, other flame retardants can also be used), add 1.0 part of a silane coupling agent (KH560), S5. Finally, add solvent (propylene glycol monomethyl ether: acetone = 2:1) to adjust the solid content to 60±3wt%.
[0041] In the prior art, little attention is paid to the thermal properties of the resin matrix and materials, especially the regulation of the glass transition temperature. In other words, the glass transition temperature of the existing materials is generally not high. In the temperature adaptability test, especially the high temperature test, the puncture resistance performance is seriously attenuated. It is not only to meet the test requirements, but also to face more challenges such as performance stability in the actual application environment. The embodiment of the present invention uses bisphenol A epoxy resin to optimize the curing temperature and curing conditions of benzoxazine, and preferably adopts a composite curing system to ensure that the material has a higher glass transition temperature; based on this, it can greatly save energy and reduce production costs.
[0042] After preparing the resin glue solution, the embodiment of the present invention performs the dipping and pressing of the aramid fabric, specifically: (1) a horizontal dipping machine can be used to dipping the functionalized aramid fabric, wherein the vehicle speed can be set to 5-10 m / min, the oven temperature is set to 140-150° C., and the glue amount is controlled to be 45-50 wt%; (2) the semi-cured sheet obtained after drying is rolled up, and then a laser cutting machine is used to cut it according to the rated size; (3) the cut aramid sheet is placed on a flat press for pressing, preferably, the starting temperature is 130° C., the pressure is 5 MPa, and the heat is kept for 60 minutes, and then the temperature is increased to 160° C., the pressure is increased to 20 MPa, and the heat is kept for 2-3 hours; (4) the temperature is naturally reduced to below 110° C., the temperature is cooled to below 60° C. by water, and then removed, and then the trimming, inspection, packaging and other processes are carried out; (5) sampling and laser cutting is performed according to the version, and testing is performed after packaging.
[0043] In the prior art, the preparation of composite materials with a high glass transition temperature usually requires a relatively high hot pressing temperature (180° C. or higher), which places high demands on equipment and energy consumption and results in a complex preparation process.
[0044] The embodiment of the present invention uses aramid fiber as the substrate, utilizes the debonding effect of DMAc / salt solution on the strong hydrogen bonding effect between aramid molecules, and uses a solution containing aramid to modify the surface of aramid filaments, which greatly improves the interface effect (i.e., interface shear force) between aramid fiber and resin matrix. At the same time, without affecting the strong effect of aramid, it avoids waste of resources and energy and improves the comprehensive stab-proof performance of the material. The embodiment of the present invention can adopt continuous dipping technology, and then adopt hot pressing process for molding, which can be replaced by similar processes, such as primer, spraying, vacuum introduction, etc., and keep the main composition of the material unchanged to achieve the approximate goal. The embodiment of the present invention prepares a high-strength resin matrix to effectively resist the first wave of impact of sharp tools such as knives; and improves the thermal stability of the composite material to meet the temperature adaptability requirements in the test standard; further improves the single-piece stab-proof performance to reduce the weight of the stab-proof layer to meet the requirements of the new standard. All materials involved in the embodiment of the present invention are domestically produced materials, and can be stably supplied to ensure the domestic production of national defense and security clothing.
[0045] The embodiment of the present invention provides a flexible stab-proof material obtained by the preparation method as described above, which uses benzoxazine resin and epoxy resin as a composite resin matrix and modified aramid fiber as a reinforcement phase. In addition, the present invention provides the use of the flexible stab-proof material as described above in security clothing and accessories such as police stab-proof clothing.
[0046] In some embodiments of the present application, the surface density of the flexible stab-proof material is 230-310 g / m 2 Range, specifically divided into 230, 270, 290, 310g / m 2 and other four models; its single-filament pull-out force can be more than 126N. The present invention has carried out a series of characterizations on the thermal properties of stab-proof materials, especially the glass transition temperature. For example, Tg can be 120-175°C. The temperature adaptability test of stab-proof materials is tested in high temperature, and a theoretical definition is given in combination with the embodiments of the present invention (that is, 130°C may be the limit temperature at which the performance of the material does not significantly decay after high-temperature treatment at 55°C). The present invention provides a material basis for the design of police stab-proof clothing under the new standard, that is, it can meet the requirements of low curvature (less than 150N) and light total mass (the stab-proof layer is only 1.36kg under the effective protection area).
[0047] In order to better understand the technical content of the present invention, the following specific examples are provided to further illustrate the present invention. In the following examples, unless otherwise specified, all are weight ratios; the raw materials used are commercially available and conventional equipment is used.
[0048] Example 1
[0049] 1. Synthesis of aramid slurry: (1) Add 100 parts of N,N-dimethylformamide to a reactor, and add 0.5 parts of CaCl2 thereto, then heat the solution to 100°C, control the stirring rate to 500r / min, and cool to 0°C after CaCl2 (cosolvent) is completely dissolved; (2) Add 10 parts of p-phenylenediamine thereto, stir at a rate of 500r / min, and after it is fully dissolved, add 18.8 parts of terephthaloyl chloride thereto in 5 portions (the number of added portions is 1 part, 3 parts, 5 parts, 5 parts, and 4.8 parts, respectively), and keep the reactor temperature not exceeding 5°C during the reaction. 0℃, the reaction time is controlled to be 4h; (3) after the reaction is completed, the HCl produced by the reaction is neutralized with calcium hydroxide until the pH of the solution is neutral (detected by moistened pH test paper), and then vacuum filtration is performed to remove impurities to obtain an aramid stock solution, wherein the solid content of the stock solution is 15-17wt%; (4) the stock solution is diluted with N,N-dimethylformamide to a solid content of 5-7wt% and an intrinsic viscosity of 3.0-3.6dL / g (the viscosity is generally tested in the reaction system and can be set to 25℃±3℃), and transferred to a closed anaerobic container for storage and standby use.
[0050] 2. Aramid fiber processing: (1) The selected aramid fiber is SF68 para-aramid filament (800D or 1000D) provided by Sinochem International, with a strength ≥16cN / dTex; the aramid fiber is placed on a bracket for wiring, the aramid stock solution is transferred into a glue tank, the aramid fiber is immersed in the aramid slurry via a guide roller, and the pulling rate is controlled to ensure that the fiber stays in the solution for 3 minutes; (2) The aramid fiber pulled out from the glue tank is immersed in a first coagulation bath, which is composed of a DMAc / H2O=70 / 30 mixed solution, wherein the CaCl2 content is 3wt%; (3) The aramid fiber pulled out from the first coagulation bath is immersed in a second coagulation bath, which is composed of a DMAc / H2O=50 / 50 mixed aqueous solution; (4) The fiber pulled out from the second coagulation bath enters a water washing device for washing, and then is dried and rolled up for standby use.
[0051] 3. Aramid fabric processing: The functionalized aramid fiber is woven into a plain fabric using a horizontal loom, with a horizontal density of 24 or 28 counts / 10cm, preferably 28 counts / 10cm, a vertical density of 28 or 32 counts / 10cm, preferably 32 counts / 10cm, and a woven fabric surface density of 165±3g / m 2 .
[0052] 4. Preparation of resin glue: S1. Add 100 parts of benzoxazine resin (bisphenol A benzoxazine resin provided by Enying Polymer, EN2108) to the reactor and heat to 110°C until it is completely transparent; S2. Cool down to 80°C, add 40 parts of solvent, and then add 30 parts of epoxy resin (E44:E51=1:1); start stirring, set the speed to 600r / min, heat to 120°C, and keep warm for 3h; S3. Add 16 parts of measured curing agent (DDS), continue to maintain 120°C, adjust the stirring speed to 1000r / min, and react for 60min; S4. Cool down with water, cool to below 40°C, continue to stir, adjust the speed to 600r / min, and add IPDA 4 parts, add 10 parts of a mixture of ammonium superphosphate and TCPP (mass ratio is 2:1), add 1.0 parts of a silane coupling agent (KH560); S5. Finally, add solvent (propylene glycol monomethyl ether: acetone = 2:1) to adjust the solid content to 60±3wt%.
[0053] 5. Fabric dipping and pressing: (1) The functionalized aramid fabric is dipped in glue using a horizontal dipping machine, wherein the machine speed is set to 8 m / min, the oven temperature is set to 145°C, the fabric is 165 g / m2 aramid fabric, and the glue application amount is controlled to be 48-50 wt%; (2) The semi-cured sheet obtained after drying is rolled up and then cut according to the rated size using a laser cutting machine; (3) The cut aramid sheet is placed on a flat press for pressing, wherein the initial temperature is 130°C, the pressure is 5 MPa, and the heat is maintained for 60 min, and then the temperature is increased to 160°C, the pressure is increased to 20 MPa, and the heat is maintained for 3 h; (4) The temperature is naturally reduced to below 110°C, and the temperature is reduced to below 60°C by water, and then removed, and then the trimming, inspection, packaging and other processes are carried out; (5) Samples are taken and laser cut according to the pattern, and then tested after packaging.
[0054] Example 2
[0055] 1. Synthesis of aramid slurry: (1) Add 100 parts of N,N-dimethylformamide to a reactor, and add 0.5 parts of CaCl2 thereto, then heat the solution to 100°C, control the stirring rate to 500r / min, and after CaCl2 (cosolvent) is completely dissolved, cool it to 0°C; (2) Add 10 parts of p-phenylenediamine thereto, stir at a rate of 500r / min, and after it is fully dissolved, add 18.8 parts of terephthaloyl chloride thereto in 5 portions (the number of added portions is 1 part, 3 parts, 5 parts, 5 parts, and 4.8 parts, respectively), and keep stirring at 100°C for 10 minutes. During the reaction, the temperature of the reactor does not exceed 50° C. and the reaction time is controlled to be 4 hours; (3) After the reaction is completed, the HCl produced by the reaction is neutralized with calcium hydroxide until the pH of the solution is neutral (detected by moistened pH test paper), and then, the solution is filtered under reduced pressure to remove impurities to obtain an aramid stock solution, wherein the solid content of the stock solution is 15-17wt%; (4) The solution is diluted with N,N-dimethylformamide to a solid content of 5-7wt% and a characteristic viscosity of 3.0-3.6dL / g, and then transferred to a sealed anaerobic container for storage and standby use.
[0056] 2. Aramid fabric processing: The selected aramid is SF68 para-aramid filament (800D or 1000D) provided by Sinochem International, with a strength of ≥16cN / dTex. The above fibers are woven into plain fabrics using a horizontal loom, with a horizontal density of 24 or 28 counts / 10cm, a vertical density of 28 or 32 counts / 10cm, and a woven fabric surface density of 165g / m 2 .
[0057] 3. Aramid fabric treatment: (1) The aramid slurry is transferred into a glue tank, and the aramid fabric is immersed in the aramid slurry via a guide roller, and the pulling rate is controlled to ensure that the fiber stays in the solution for 5 minutes; (2) The aramid fiber pulled out from the glue tank is immersed in the first coagulation bath, which is composed of a DMAc / H2O=70 / 30 mixed solution, wherein the CaCl2 content is 3wt%; (3) The aramid fiber pulled out from the first coagulation bath is immersed in the second coagulation bath, which is composed of a DMAc / H2O=50 / 50 mixed aqueous solution; (4) The fiber after the second coagulation bath enters a water washing device for washing, and then after drying, it is rolled up for standby use.
[0058] 4. Preparation of resin glue: S1. Add 100 parts of benzoxazine resin (bisphenol A benzoxazine resin provided by Enying Polymer, EN2108) to the reactor and heat to 110°C until it is completely transparent; S2. Cool down to 80°C, add 40 parts of solvent, and then add 30 parts of epoxy resin (E44:E51=1:1); start stirring, set the speed to 600r / min, heat to 120°C, and keep warm for 3h; S3. Add 16 parts of measured curing agent (DDS), continue to maintain 120°C, adjust the stirring speed to 1000r / min, and react for 60min; S4. Cool down with water, cool to below 40°C, continue to stir, adjust the speed to 600r / min, and add IPDA 4 parts, add 10 parts of a mixture of ammonium superphosphate and TCPP (mass ratio is 2:1), add 1.0 parts of a silane coupling agent (KH560); S5. Finally, add solvent (propylene glycol monomethyl ether: acetone = 2:1) to adjust the solid content to 60±3wt%.
[0059] 5. Fabric Dipping and Pressing: (1) A horizontal dipping machine is used to dip the functionalized aramid fabric. The machine speed is set at 8 m / min, the oven temperature is set at 145°C, and the fabric is 165 g / m 2 aramid fabric, controlling the glue amount to 48-50wt%; (2) rolling up the semi-cured sheet obtained after drying, and then cutting it according to the rated size using a laser cutting machine; (3) placing the cut aramid sheet on a flat press for pressing, wherein the initial temperature is 130°C, the pressure is 5MPa, and the heat preservation is carried out for 60min, and then the temperature is increased to 160°C, the pressure is increased to 20MPa, and the heat preservation is carried out for 3h; (4) naturally cooling to below 110°C, cooling to below 60°C with water, removing it, and then carrying out processes such as trimming, inspection, and packaging; (5) sampling and laser cutting according to the version, and testing after packaging.
[0060] Example 3
[0061] Steps 1 to 3 are the same as those in Example 1.
[0062] 4. S1. Add 100 parts of benzoxazine resin (bisphenol A benzoxazine resin provided by Enying Polymer, EN2108) to the reactor and heat to 110°C until it is completely transparent; S2. Cool down to 80°C, add 40 parts of solvent, and then add 50 parts of epoxy resin (E44:E51=1:1) in sequence; start stirring, set the speed to 600r / min, heat to 120°C, and keep warm for 3h; S3. Add 22 parts of measured curing agent (DDS), continue to maintain 120°C, adjust the stirring speed to 1000r / min, and react for 60min; S4. Cool down with water to below 40°C, continue to stir, adjust the speed to 600r / min, and add IPDA 6 parts, add 10 parts of a mixture of ammonium superphosphate and TCPP (mass ratio is 2:1), add 1.0 parts of a silane coupling agent (KH560); S5. Finally, add solvent (propylene glycol monomethyl ether: acetone = 2:1) to adjust the solid content to 60±3wt%.
[0063] Step 5 is the same as in Example 1.
[0064] Example 4
[0065] Steps 1 to 3 are the same as those in Example 1.
[0066] 4. S1. Add 100 parts of benzoxazine resin (bisphenol A benzoxazine resin provided by Enying Polymer, EN2108) to the reactor and heat to 110°C until it is completely transparent; S2. Cool down to 80°C, add 40 parts of solvent, and then add 100 parts of epoxy resin (E44:E51=1:1) in sequence; start stirring, set the speed to 600r / min, heat to 120°C, and keep warm for 3h; S3. Add 44 parts of measured curing agent (DDS), continue to maintain 120°C, adjust the stirring speed to 1000r / min, and react for 60min; S4. Cool down with water, cool to below 40°C, continue to stir, adjust the speed to 600r / min, and add IPDA 12 parts, add 10 parts of a mixture of ammonium superphosphate and TCPP (mass ratio is 2:1), add 1.0 parts of a silane coupling agent (KH560); S5. Finally, add solvent (propylene glycol monomethyl ether: acetone = 2:1) to adjust the solid content to 60±3wt%.
[0067] Step 5 is the same as in Example 1.
[0068] Example 5
[0069] Steps 1 to 3 are the same as those in Example 1.
[0070] 4. S1. Add 100 parts of benzoxazine resin (bisphenol A benzoxazine resin provided by Enying Polymer, EN2108) to the reactor and heat to 110°C until it is completely transparent; S2. Cool down to 80°C, add 40 parts of solvent, and then add 50 parts of epoxy resin (E44:E51=1:1) in sequence; start stirring, set the speed to 600r / min, heat to 120°C, and keep warm for 3h; S3. Add 28 parts of curing agent (DDS) , continue to maintain 120°C, adjust the stirring speed to 1000r / min, and react for 60min; S4. Cool down with water to below 40°C, continue to stir, adjust the speed to 600r / min, add 10 parts of a mixture of ammonium superphosphate and TCPP (mass ratio is 2:1), and add 1.0 part of a silane coupling agent (KH560); S5. Finally, add solvent (propylene glycol monomethyl ether: acetone = 2:1) to adjust the solid content to 60±3wt%.
[0071] Step 5 is the same as in Example 1.
[0072] Comparative Example 1
[0073] After untreated aramid is used to weave a plain fabric, it is dipped in glue; the steps of preparing the glue solution are the same as step 4 of Example 1.
[0074] The step of pressing the fabric is the same as step five of Example 1 to obtain a stab-proof material.
[0075] Comparative Example 2
[0076] Steps 1 to 3 are the same as those in Example 1.
[0077] 4. S1. Add 100 parts of benzoxazine resin (bisphenol A benzoxazine resin provided by Enying Polymer, EN2108) into the reactor and heat to 110°C until it is completely transparent; S2. Cool down to 80°C and add 40 parts of solvent; start stirring and set the speed to 600r / min. After heating to 120°C, keep warm for 3h; S3. Cool down with water to below 40°C, continue stirring, adjust the speed to 600r / min, add 10 parts of a mixture of ammonium superphosphate and TCPP (mass ratio is 2:1), and add 1.0 part of a silane coupling agent (KH560); S4. Finally, add solvent (propylene glycol monomethyl ether: acetone = 2:1) to adjust the solid content to 60±3wt%.
[0078] Step 5 is the same as in Example 1.
[0079] Comparative Example 3
[0080] Steps 1 to 3 are the same as those in Example 1.
[0081] 4. S1. Add 100 parts of bisphenol A epoxy resin (E44: E51 = 1:1) into the reactor and heat to 110°C until it is completely transparent; S2. Cool down to 80°C and add 40 parts of solvent; start stirring, set the speed to 600r / min, add 63 parts of 4,4-diaminodiphenyl sulfone, raise the temperature to 120°C, adjust the speed to 1000r / min, and keep warm for 1h; S3. Cool down with water to below 40°C, continue stirring, adjust the speed to 600r / min, add 10 parts of a mixture of ammonium superphosphate and TCPP (mass ratio is 2:1), and add 1.0 part of a silane coupling agent (KH560); S4. Finally, add solvent (propylene glycol monomethyl ether: acetone = 2:1) to adjust the solid content to 60±3wt%.
[0082] Step 5 is the same as in Example 1.
[0083] Conventional standard tests and dynamic tests were performed on the samples obtained in the examples and comparative examples, and the test results are shown below.
[0084] Figure 1 This is the curing peak temperature fitting curve of the resin system of the embodiment of the present invention; the test conditions are: 40℃~300℃, and the heating rates are 5, 10, and 15℃ / min respectively, which is mainly used to measure the processing conditions, namely the curing temperature. Figure 1 , the curing temperature exceeds 157°C.
[0085] Figure 2 is the DSC test curve of the samples of Example 1 and Example 2 (tested by differential scanning calorimeter, the test conditions are 25°C to 300°C, and the heating rate is 10°C / min), Figure 2 The black curve in the middle shows that the Tg of the sample of Example 1 is about 173°C, and the red curve shows that the Tg of the sample of Example 2 is about 171°C. Figure 3 The figure shows the dipping conditions of the samples of Examples 1-3 of the present invention, illustrating the uniformity.
[0086] Table 1 Test results of stab-resistant material samples obtained in the embodiments of the present invention and the comparative examples
[0087]
[0088] From the above test results, it can be seen that the samples of Examples 1-3 can meet the puncture resistance test, show high puncture force in the quasi-static puncture experiment, and show high uniformity under an optical microscope (such as Figure 3 As shown). Among them, Example 1 shows the best comprehensive performance (its fabric functionalization treatment effect is more ideal than that of Example 2); when the protection area is 0.25m 2Under the condition of , the mass of the stab-proof material is only 1.36kg. Under the requirement that the total mass of the police stab-proof clothing is ≤1.8kg, there is a large space for the design of the stab-proof material protective cover and the stab-proof clothing jacket. The experimental results further show that if the Tg, that is, the glass transition temperature of the resin, is less than 130°C, it will be difficult to meet the high temperature test requirements in the temperature adaptability test; under the same curing conditions, the Tg of the pure benzoxazine resin is low and uneven, indicating that the resin has insufficient fluidity during the pressing process and is not completely cured. At the same time, it is further explained that the mixed resin system and composite curing system adopted by the present invention can effectively reduce curing problems and improve curing efficiency. The embodiment of the present application adopts a stab-proof layer with a total surface density of 5.45kg / m 2 Compared with the previous stab-proof clothing surface density (> 8kg / m 2 ) is lighter.
[0089] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0090] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only used to help understand the method and core ideas of the present invention. The above is only a preferred implementation of the present invention. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the inventive concept and technical solution to other occasions without improvement, should be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a flexible stab-proof material, characterized in that: The following steps are involved: Providing a nano-aramid aqueous dispersion or an aramid slurry, wherein the aramid slurry comprises an aramid resin, an amide solvent and a cosolvent; The nano-aramid aqueous dispersion or aramid slurry is used to modify the surface of aramid fibers by dipping to form a functionalized aramid fabric, which is then compounded with a resin adhesive system comprising a benzoxazine resin, an epoxy resin and a curing agent to obtain a flexible stab-proof material.
2. The method for preparing the flexible stab-proof material according to claim 1, characterized in that: The aramid slurry has a solid content of 5-7wt% and an intrinsic viscosity of 3.0-3.6dL / g.
3. The method for preparing the flexible stab-proof material according to claim 1, characterized in that: The aramid slurry is obtained by the following operation: phenylenediamine and phthaloyl halide are polymerized through low-temperature solution, and then neutralized, impurity-removed and diluted to obtain the aramid slurry containing aramid resin.
4. The method for preparing the flexible stab-proof material according to any one of claims 1 to 3, characterized in that: The aramid resin is para-aramid, the amide solvent is N,N-dimethylformamide, and the co-solvent is calcium chloride.
5. The method for preparing the flexible stab-proof material according to claim 4, characterized in that: The surface modification comprises: selecting para-aramid fiber filaments or para-aramid fiber fabrics, immersing them in the nano-aramid aqueous dispersion or aramid slurry for 3 minutes, then shaping them in a coagulation bath, washing and drying to obtain functionalized aramid fibers.
6. The method for preparing the flexible stab-proof material according to claim 5, characterized in that: The strength of the para-aramid fiber filament is ≥16 cN / dTex, the functionalized aramid fiber is processed into a functionalized aramid fabric, and the surface density of the functionalized aramid fabric is 165-260 g / m 2 .
7. The method for preparing the flexible stab-proof material according to any one of claims 1 to 3, characterized in that: The benzoxazine resin is one or more of bisphenol A benzoxazine, bisphenol F benzoxazine, MDA benzoxazine, ODA benzoxazine and composite benzoxazine; the epoxy resin is bisphenol A epoxy resin; the curing agent is one or more of dicyandiamide, 4,4-diaminodiphenyl sulfone, polyamide, isophordione diamine and diaminodiphenylmethane.
8. The method for preparing the flexible stab-proof material according to claim 7, characterized in that: The compounding with the resin adhesive system comprises: immersing the functionalized aramid fabric in a resin adhesive solution, drying, and controlling the adhesive amount to be 45-50wt%; the resin adhesive solution comprises benzoxazine resin, epoxy resin, curing agent, flame retardant, silane coupling agent and solvent; The semi-cured sheet obtained after drying is pressed at a temperature of 130 to 160 degrees Celsius, and the pressing pressure is 5 to 20 MPa to obtain a flexible stab-proof material.
9. The flexible stab-proof material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the flexible stab-proof material according to claim 9 in security clothing and accessories.
Citation Information
Cited By
Modified para-aramid stock solution, preparation method and para-aramid fiber thereof
CN120209298A
